Moorish Brother: Freemasonry and Colonialism in Spanish Protectorate of Morocco (1931-1936) - Aguiar Bobet, Valeria (2018)
For the Spanish Masons, the "Muslim brother", title of this article, is not a Mason more, he is an exceptional brother constructed from the colonial canon and the common shared past in a medieval distorted epoch, a historical but childish brother, necessary to legitimize the Masonic performance in the North of Africa. In this respect, the text addresses the construction of the image of the "other Muslim"by analyzing of the colonial discourse of the Hispanic Freemasonry implanted in the Moroccan protectorate since the late 19th century. However, last but not least, the consequences and particularities that the discursive limits of both variables (the construct and his reception) will suppose for the attainment of the ideal colonial Masonic projected by the North African lodges.